Nitrogen isotope evidence for an oligotrophic shallow ocean during the Cambrian Stage 4. (15th July 2019) - Chang, Chao; Hu, Wenxuan; Wang, Xiaolin; Huang, Kang-Jun; Yang, Aihua; Zhang, Xingliang
Abstract: Following the Cambrian Explosion, a significant extinction event occurred during the Cambrian Stage 4, with the extinction rate second only to that experienced in the end-Permian. To figure out the variation of N supply and elucidate the combined effect of O2 and N availability on the extinction event, this study presents the first set of high-resolution N isotope data from two shallow-water Cambrian Stage 4 drilling sections on the eastern Yangtze Platform. The results indicate that the sections are characterized by highly negative δ 15 N signatures during the lowermost and uppermost Cambrian Stage 4, which are indicative of strong NH4 + assimilation in an anoxic shallow ocean. During the rest of the Cambrian Stage 4, both of the study sections show stable δ 15 N values close to 0. This phenomenon can be best explained by enhanced N2 fixation in an oxic shallow ocean characterized by strong N limitation, resembling the low-latitude oligotrophic regions in the modern ocean. The oligotrophic environment was likely caused by enhanced denitrification/anammox as well as elevated P input associated with eustatic changes, and may have been widespread in the global shallow ocean during the Cambrian Stage 4. Our results lend new support to the traditional view that anoxia contributed to the mass extinction event. More importantly, it is emphasized that the oligotrophic environment may have played an important role in the prolonged decline of metazoan diversity during this stage.